Revealing Architecture: Case of the Sacred Cultural Landscape of Ekamrakshetra, Bhubaneswar - Das, Piyush (MAJ - Malaysia Architectural Journal, 2023)
The historic sacred cultural landscape of Bhubaneswar (Ekamrakshetra or the region of one mango tree) has diverse cultural resources both tangible and intangible which can be categorized under cultural and natural. The built resources which are comprised of temples, mathas (institutional), water tanks of various types (Pokhari, Sagara, Kunda, and so on), etc are very significant and their architectonics are unique to understand when seen and perceived from the lenses of the local practices, rituals, and other activities under the sacred realm. The continuing landscape, where the traditions and customs etc are still in practice, the built finds new meaning and narrative. It reveals as per the ritual. It reveals as per the time. For example, as per one ritual, one needs to take a dip in Bindusagara (the largest water body) early morning and experience breathlessness for a moment, and get up. Then while the water level is at the chest, one has to face east and pray to the Sun god. Then one looks in the northeast direction and sees the amalaka (the top part of a temple’s sikhara) of a shrine of a particular deity, then closes eyes and prays. And so on. A curated pathway, varied itineraries of seeing and looking, the idea of none seeing (closing eyes and praying), and many such actions are the part of everyday rituals and practices of that place. The perception of the same curated experiences changes based on the time of the day. It changes based on the season or a time of a particular festival. The built in the landscape reveals the norms of these sacred systems, which one finds mentions in the regional texts such as Swarnadri Mahodaya, Ekamra Chandrika1, etc which describe the sacred landscape and other related entities. The pieces of evidence of the experiences and perceptions can be attained only by true knowledge. As per Nyaya-sutra2 supreme felicity or nirsreyasa is attained by true knowledge. This paper attempts to comprehend the idea of revealing architecture by understanding the primary texts describing the place and builds a new narrative for the architecture of the sacred cultural landscape of Bhubaneswar while referring to Nyaya sutra theories. The methodologies may be considered more holistic than the conventional method of seeing and perceiving architecture in the context of Ekamrakshetra.